ANSWER
• x = 12
,
• y = 16
,
• z = 7
Step-by-step explanation
Because the triangles are similar, we have that:
• The ratio between corresponding sides is constant:
![(DE)/(GH)=(EF)/(GF)=(DF)/(HF)](https://img.qammunity.org/2023/formulas/mathematics/college/q6m1nzotvma7gz53kiy1bgqcvmx2u4tofm.png)
• Corresponding angles are congruent:
![\begin{gathered} \angle D\cong\angle H \\ \angle E\cong\angle G \\ \angle F\cong\angle F \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/moo6xsz4n0ominh7opvoa1nfqcoh4q7147.png)
We know that the measure of angle E is 16°, so the measure of angle G must be the same because they are congruent,
![16\degree=2(x-4)\degree](https://img.qammunity.org/2023/formulas/mathematics/college/370ri5n03em75v4rnw4scbcqllnsz1qxpx.png)
With this equation, we can find x. First, divide both sides by 2,
![\begin{gathered} (16)/(2)=(2(x-4))/(2) \\ \\ 8=x-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/711kqafhn8ix98fxsufi9n7cj3i3f7sr49.png)
And then, add 4 to both sides,
![\begin{gathered} 8+4=x-4+4 \\ \\ 12=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/dj1no349lh0uj9xwmklq4savaj7r7o7jpj.png)
Hence, x = 12.
Now we know that the length of side EF is,
![EF=x-5=12-5=7](https://img.qammunity.org/2023/formulas/mathematics/college/7upiupwkj7tt12yc8vyzoajk5b79lkebml.png)
To find y and z, we will use the proportions we got at the top of this explanation,
![(DE)/(GH)=(EF)/(GF)=(DF)/(HF)](https://img.qammunity.org/2023/formulas/mathematics/college/q6m1nzotvma7gz53kiy1bgqcvmx2u4tofm.png)
Replace with the known values and the expressions with y and z,
![(25)/(6z+8)=(7)/(14)=(24)/(3y)](https://img.qammunity.org/2023/formulas/mathematics/college/ylpbrfps7ecbln9fxmf3v53cjeo6zhe35n.png)
With the first two, we can find z,
![(25)/(6z+8)=(7)/(14)](https://img.qammunity.org/2023/formulas/mathematics/college/944tk3l5qw611agldzo47wtpefu4mh6h8n.png)
Simplify the right side,
![(25)/(6z+8)=(1)/(2)](https://img.qammunity.org/2023/formulas/mathematics/college/bw3inzw2jvh41hhcmff3wmn1t4afyb33in.png)
Rise both sides to the exponent -1 - i.e. flip both sides of the equation,
![(6z+8)/(25)=2](https://img.qammunity.org/2023/formulas/mathematics/college/ky9d7as4cbe8vgm9qbg46ai7dprazbtt2x.png)
Multiply both sides by 25,
![\begin{gathered} 25\cdot((6z+8))/(25)=2\cdot25 \\ \\ 6z+8=50 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/457giqeiundgmaiowdw25bu60kz8kswg1j.png)
Subtract 8 from both sides,
![\begin{gathered} 6z+8-8=50-8 \\ 6z=42 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rq13ccxok0r5qqn05dimpqg8sb8p48hd2n.png)
And divide both sides by 6,
![\begin{gathered} (6z)/(6)=(42)/(6) \\ \\ z=7 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6kyjn4woaytn11cq6f2et8x4ac5e1uf2lx.png)
Hence, z = 7.
Finally, with the last two proportions, we can find y,
![(7)/(14)=(24)/(3y)](https://img.qammunity.org/2023/formulas/mathematics/college/1wcmhanps830bu79vb5lotkaxtxkk2h2da.png)
The first two steps are the same we did to find z: simplify the left side and flip both sides,
![2=(3y)/(24)](https://img.qammunity.org/2023/formulas/mathematics/college/tz8kd14qx65rdt9kla4lxp2uhod6mzso9v.png)
Multiply both sides by 24,
![\begin{gathered} 24\cdot2=24\cdot(3y)/(24) \\ \\ 48=3y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rq57r6ia1y648hu6zccjgfur29k2635umw.png)
And divide both sides by 3,
![\begin{gathered} (48)/(3)=(3y)/(3) \\ \\ 16=y \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/r0cxopm5j8wbv3wtzfp41s2edq9lfiz1ay.png)
Hence, y = 16.